Reciprocal Mentoring Residencies: Better transitions to teaching - Paris, Lisa (Edith Cowan University, 2010)
The 2007 "Top of the Class" report on the Inquiry into Teacher Education in Australia found teacher induction failure and high attrition rates were endemic in most Australian states. Mentoring was advocated as an important mechanism for countering the debilitating drain attrition exerted on the profession (more than 30% within the first years in most developed nations). Reciprocal mentoring represents a departure from traditional mentoring arrangements in that it aligns two professionals with skills of equivalent importance and stature but in different discipline areas/domains. The importance of "reciprocity" in sustaining mentoring relationships is a distinctive theme in the conceptual framework for the model. In 2010 Graduate Diploma pre-service teachers from visual arts, music, drama and mathematics will be matched to mentors in reciprocal mentoring residencies in the first formal study of the mentoring innovation. This paper acts in the capacity of a prolegomena, describing the work undertaken to date and over-viewing the reciprocal mentoring which will occur in 2010.